An attempt to understand the dialog in philosophy of M. Buber (in parallel with T. Sodeika’s interpretation) - Gutauskas, Mintautas (Religija ir kultūra, 2008)
There are radical and moderated trends in Buber’s thought and its interpretation. The aim of this article is to present moderated interpretation of the notion of dialog in Bubers philosophy. Such interpretation is treated as parallel to radical T. Sodeika’s interpretation. From the perspective of phenomenology, this article analyzes possibilities to distinguish communication and dialog, examines what role plays experience and encounter in the dialog, how I-Thou relationship establishes space and time of the dialog.
Keywords: Buber; dialog; communication; encounter